Pharmacokinetic/pharmacodynamic relationships of antimicrobial drugs used in veterinary medicine - McKellar, Quintin A. (2004)
The rise in incidence of antimicrobial resistance, consumer demands and improved understanding of antimicrobial action has encouraged international agencies to review the use of antimicrobial drugs.  More detailed understanding of relationships between the pharmacokinetics (PK) of antimicrobial drugs in target animal species and their action on target pathogens [pharmacodynamics (PD)] has led to greater sophistication in design of dosage schedules which improve the activity and reduce the selection pressure for resistance in antimicrobial therapy.  This, in turn, may be informative in the pharmaceutical development of antimicrobial drugs and in their selection and clinical utility.  Pharmacokinetic/PD relationships between Area Under the Concentration time curve from zero to 24h (AUC0-24) and Minimum Inhibitory Concentration (MIC), maximum plasma concentration (Cmax) and MIC and time during which plasma concentrations exceed the MIC have been particularly useful in optimising efficacy and minimising resistance.   Antimicrobial drugs have been classified as concentration-dependent where increasing concentrations at the locus of infection improve bacterial kill, or time-dependent where exceeding the MIC for a prolonged percentage of the inter-dosing interval correlates with improved efficacy.  For the latter group increasing the absolute concentration obtained above a threshold does not improve efficacy.  The PK/PD relationship for each group of antimicrobial drugs is ´bug and drug´ specific, although ratios of 125 for AUC0-24:MIC and 10 for Cmax :MIC have been recommended to achieve high efficacy for concentration-dependent antimicrobial drugs, and exceeding MIC by 1-5 multiples for between 40% and 100% of the inter-dosing interval is appropriate for most time-dependent agents.  Fluoroquinolones, aminoglycosides and metronidazole are concentration-dependent and beta lactams, macrolides, lincosamides and glycopeptides time-dependent. For drugs of other classes there is limited and conflicting information on their classification.   Resistance selection may be reduced for concentration-dependent antimicrobials by achieving an AUC0-24:MIC ratio of greater than 100 or a Cmax:MIC ratio of greater than eight. The relationships between time greater than MIC and resistance selection for time-dependent antimicrobials have not been well characterised.